Ecological aspects of meranti kunyit (Shorea macroptera Dyer) in Rantau Bertuah Forest, Siak Regency, Riau Province and the implication for forest management and conservation - Rizki Ary Fambayun; Nur Muhammad Heriyanto; Marfuah Wardani (Foresty Faculty of Hasanuddin University, 2022)
Sumatra’s lowland tropical rainforest is in the third place after Kalimantan and Papua in terms of Indonesia’s plant species diversity. Shorea macroptera is one of the species from the Dipterocarpaceae family, known as an important commercial timber tree species. In September 2019, the study was conducted in Rantau Bertuah Forest, Siak Regency, Riau Province, Sumatra, with a total sample plot area of 1 ha. The data were analyzed to show the vegetation quantitative structure and composition on the study site using the Important Value Index, and the association of S. macroptera using the Ochiai index. The results recorded 55 plant species belong to 33 families on this study site. Dipterocarpaceae, Euphorbiaceae, and Fabaceae have the most abundant species, encompassed 51 species ≥10 cm in diameter with a total of 624 individuals. The result showed that the top three dominant species in this area, namely Callophyllum macrocarpum Hook.f. (IVI = 27.88%), Shorea parvifolia Dyer (IVI = 21.98%) and Gironniera nervosa Planch. (IVI = 19.99%). C. macrocarpum dominated all the regeneration levels: tree, sapling and seedling with IVI of 27.88%, 49.57% and 86.31%, respectively. S. macroptera has the strongest association with C. macrocarpum (Ochiai index of 0.73), followed by the S. parvifolia (Ochiai index of 0.61) and G. nervosa species (Ochiai index of 0.51). S. macroptera is widely used for industrial timber purposes and has limited distribution. Therefore, it is necessary to increase the efforts to manage it sustainably, especially in production forests.